The Specificity of the Provisions of Punishment in Cybercrime of State Security in UAE Legislation - Suleiman, Mohammed; Sayed, Muhammad (Journal of Legal Sciences, 2026)
The research dealt with the specificity of the provisions of punishment in state security information crimes in the UAE legislation, highlighting the most prominent penalties stipulated by the UAE legislator in Federal Decree-Law No. (34) Of 2021 regarding rumors and cybercrimes, where the problem of the study revolves around the adequacy of the penalties stipulated by the UAE legislator in reducing state security information crimes. The importance of the research from a scientific point of view is that it is specialized research to study the privacy feature in state security information crimes, especially since the UAE legislator stipulated many provisions for punishment for these crimes, and the UAE legislator has a special policy for punitive individualization of these crimes, different from punitive individualization in the Federal Crimes and Penal Code, meaning that the research specializes in these penalties without delving into the general context of the provisions of penalties in state security crimes, and the research is considered one of the first Legal research on showing, clarifying and identifying the elements of privacy in the provisions of punishment for state security information crimes, as it benefits a group of jurists, lawyers and law students Due to the seriousness of state security cybercrimes, the UAE legislator has singled them out with special rules for punishment, especially in Federal Decree-Law No. (34) of 2021 on combating rumors and cybercrime, and therefore the UAE legislator did not make the rules of punishment for these crimes uniform in terms of aggravating circumstances and mitigating circumstances, nor did it provide special provisions for exemption with regard to information state security crimes, and therefore the research problem revolves around the following question: How adequate, are the punishment provisions for state security cybercrimes sufficient to achieve privacy to punish these crimes? One of the most prominent results of the study is that the penalties and measures mentioned by the UAE legislator in its legislative policy in combating state information security crimes are sufficient in themselves to reduce these crimes, and one of the recommendations of the study is the need for the UAE legislator to tighten some penalties for these crimes.